Pengolahan Sampah Plastik Menjadi Ecobrick (Sofa) Dalam Upaya Mengurangi Sampah Plastik di SMPN 16 Mataram - Gunawan, Rendi; Hijrotussulusi; Nadia, Dea; Hidayatullah , Nisa (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Waste is one of the problems that become a problem in various regions. Waste is the main factor causing various kinds of disasters, such as infectious diseases, environmental pollution, and the sustainability of living things. For this reason, this article aims to provide education to residents of SMPN 16 Mataram as a solution to reduce plastic waste in the school environment by processing plastic waste into appropriate and economically valuable goods, namely ecobricks. The method or stage for processing plastic waste into ecobricks is to provide socialization to students about ecobricks, from understanding, benefits and uses, preparing tools and materials used, collecting waste and plastic bottles, sorting waste, washing waste and collected bottles, drying and cleaning plastic waste, cutting clean garbage, filling bottles with plastic waste, putting bottles together and stringing bottles, and coating bottles that have been put together with plywood and foam. The results of this activity received a positive response from residents of SMPN 16 Mataram, can minimize plastic waste in the school environment, and make ecobricks (sofas).